Studies on shelf life of Azospirillum lipoferum, Bacillus megaterium and Pseudomonas fluorescens in vemicompost carrier - K. Saravanakumar, A. Gandhi (Journal of Phytology, 2009)
Inoculation of bioinoculants in crop cultivation plays very important role in sustainable farming. It is well known that the carrier-based bioinoculants are being very effective as carrier determines the shelf life of the inoculant. Hence the selection of better carrier is very essential for maintaining shelf life of the inoculant during storage and for better performance in the field use. In the present study, the effect of Vermicompost in maintaining the shelf life of bioinoculant such as Azospirillum lipoferum, Bacillus megaterium and Pseudomonas fluorescens was studied up to 12 months from the date of preparation of inoculant by comparing with lignite carrier. Comparatively, Vermicompost based bioinoculants showed longer shelf life than lignite based bioinoculants. Among Vermicompost based bioinoculants B. megaterium showed maximum population of 7.60 x 10 8 cfu/g of dry wt on 360th day followed by Pseudomonas 10 8 cfu/g of dry wt respectively.